Regeneration capacity and threats to mangrove areas on the southern coast of Oriental Mindoro, Philippines: Implications to mangrove ecosystem rehabilitation - AARON FROILAN RAGANAS; ANNALEE S. HADSALL; NELSON M. PAMPOLINA; STEFAN HOTES; DAMASA B. MAGCALE-MACANDOG (Society for Indonesian Biodiversity, 2020)
Abstract. Raganas AFM, Hadsall AS, Pampolina NM, Hotes S, Magcale-Macandog DB. 2020. Regeneration capacity and threats to mangrove areas on the southern coast of Oriental Mindoro, Philippines: Implications to mangrove ecosystem rehabilitation. Biodiversitas 21: 3625-3636. Regeneration capacity is important as it determines the fate of an ecosystem. This study assessed six mangrove areas in the southern coast of Oriental Mindoro, Philippines to evaluate their regeneration capacity status. Four mangrove ecotypes were delineated namely seaward, middle, landward and riverine zones at each mangrove ecosystem, where dominant mangrove species were identified and selected for regeneration capacity study. Three subplots measuring 1 x 1 m2 were laid within the five 10 x 10 m2 survey plots established per zone. The juveniles were counted and categorized according to their height classes, using linear regeneration sampling method; where: RCI (?40 cm) considered seedlings; RCII (41-150 cm) as saplings; and RCIII (151-?300 cm) as small trees. Potential threats both anthropogenic and natural were determined through key informant interviews. Seven dominant species were identified across ecotypes in all mangrove sites, namely Avicennia marina, Avicennia rumphiana, Ceriops decandra, Rhizophora apiculata, Rhizophora mucronata, Sonneratia alba, and Xylocarpus granatum. RCI (seedlings) is the most abundant across mangrove sites irrespective of the dominant species. Fishpond operation within the mangrove stand is considered a major threat to the juveniles and most mangrove ecosystems. Therefore, protection and constant monitoring of these mangrove ecosystems are necessary to ensure regeneration success in the future.